Students' Perceptions of Husain Basyaiban's Preaching Content on TikTok and Its Influence on Character Formation at MAN 1 Tuban - Nur Aida Fitria Kusuma Putri; Sholikah (Mazidah: Journal Of Educational Research, 2025)
The development of information and communication technology in the Society 5.0 era has brought significant changes to the field of education, particularly in shaping the character of the younger generation. Social media platforms such as TikTok have become an integral part of adolescents’ lives, serving not only as a source of entertainment but also as a medium for learning and digital da’wah. One of the young preachers who actively utilizes TikTok for da’wah is Husyain Basyaiban, who is well known for his simple, communicative, and easily understood preaching style among students. This study aims to explore students’ perceptions of Husyain Basyaiban’s da’wah content on TikTok and to analyze its influence on the development of students’ social and moral character at MAN 1 Tuban. The research employed a qualitative approach with a descriptive case study design. Data were collected through interviews, observations, and documentation involving students and teachers as research informants. The findings indicate that Husyain Basyaiban’s da’wah content contributes positively to character development, particularly in fostering values of empathy, responsibility, honesty, discipline, and politeness. Through a light and youth-oriented communication style, his da’wah content effectively enhances students’ moral awareness and encourages positive behavioral changes. These findings suggest that social media can be constructively utilized as an educational tool to strengthen character education when supported by proper guidance from teachers and parents in the digital era.